Innovation in the Development of the Qurban Savings Application (TAQUR) at the DKM Musholla Manbaul Iman, Tegal City - Prihadi, Deddy; Irawan, Bei Harira; Budiyanto, Muhammad Andi; Prasetyo, Faiz Irsyad; Wicaksono, Muhammad Siddik Erdi; Hapsari, Yustia; Rahmadani, Rezkiyah; Jalil, Mahben (ASEAN Journal of Empowering Community, 2024)
The Manbaul Iman Prayer Room in Tegal City faces obstacles in managing qurban savings which are still done manually, often causing recording errors and delays in reporting. This hampers transparency and efficiency in the management of qurban funds, which has an impact on the trust of the congregation. Therefore, this community service topic was chosen to introduce innovation through the development of the Qurban Savings Application (TAQUR) to improve the quality of qurban fund management at DKM Musholla Manbaul Iman. The aim of this service is to improve digital literacy and the skills of DKM managers in using information technology through implementing the TAQUR application. The methods used include needs analysis, design, development and application implementation, followed by digital literacy training for 10 DKM managers. The results of the activity showed an increase in managers' hard skills in using applications by 75%, as well as an increase in soft skills in financial management by 60%. From an economic perspective, there has been an increase in transparency accompanied by an increase in the amount of Qurban savings by 40%. The results of this service are important because they show that technological innovation can increase efficiency and trust in the management of Qurban funds, so it is worthy of being used as a model for other DKM.